Croatian Education in the Late 19th and Early 20th Century, as Scene of the Battle for Women's Rights (Training and Practice : Journal of Educational Sciences, 2011)
19th century was the era of explicit illiteracy in Croatia, while does not depend exclusivly on the level of urbanism but also on sex. In the interest of decreasing illiteracy among women they tried to focus on education policy. But it was under the authority of men, whose majority still believed in patriarchalism. A certain positive attitude towords women's education can be seen with the opening of upper grade all-female schools. Their curricula focused on the forming of a female identity: the ideal of mother, wife and housewife roles. They did not only denied women's public activity, but they also differentiated among them some would give orders, some would be maids. Sex discrimination was a bit moderated however it remained present in schools that could be seen in the disadvantaged role of female teachers comparing with their male collegaues.